Constructing a food retail environment that encourages healthy diets in cities: the contribution of local-level policy makers and civil society - Dalia Mattioni (The International Journal of Sociology of Agriculture and Food, 2021)
Faced with growing rates of malnutrition, food environments play a key role in shaping eating habits and in helping transition towards healthy diets. Much of the attention on food environment policies has been directed at the national level. Less attention has been devoted to what happens at local level, at the measures being taken by local government policy makers and by other local-level actors to encourage healthier diets, especially in cities. The objective of this article is thus to give an overview of the contribution “from below” to the construction of healthier food environments, that is, to shed light on the specific contribution of local-level policies and initiatives in making nutritious food more available, affordable, and desirable and conversely in making unhealthy foods, such as fast foods and ultra-processed foods, less so. In doing so, it focuses on the retail food environment (RFE) as a specific contribution of cities. A critical review of evaluated local-level policies sheds light on the nature and effectiveness of different types of interventions and on the complementary actions of local government and civil society, where the latter contributes to communicating a different way of “knowing” food in line with a greater appreciation of healthier foods, and to advocating for an integration of sustainability aspects in the transition towards healthy diets. The article reflects upon areas where further efforts and adjustments are needed to make interventions more effective, and emphasizes the need to continue supporting local-level civil society RFE actions, and ensure coordination and coherence between different players and between different administrative levels.